MAKNA AKTA YANG DIBUAT OLEH CALON NOTARIS MAGANG PASAL 16A AYAT (2) UNDANG-UNDANG NOMOR 2 TAHUN 2014 TENTANG JABATAN NOTARIS - I Komang Suardana (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2014)
Abstract The addition of Article 16A (2) of the prospective notary internship in law No. 2 of 2014 on the notary office, in the article there is a phrase that is confusing, that the phrase